Taxonomy of the leafhopper genus Favintiga (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) with description of a new species from China - Xu, Deliang; Zhang, Yalin (Zootaxa, 2022)
The leafhopper genus Favintiga Webb (Cicadellidae: Deltocephalinae: Drabescini: Paraboloponina) is reviewed with description of a new species, Favintiga polyacantha sp. nov., from China (Hainan). A checklist with distributions and a key to males of this genus are provided. Type specimens are deposited in the Entomological Museum, Northwest A&F University, Yangling, Shaanxi, China (NWAFU).